A Critical Review on the Efficacy of Integrated Child Development Service Scheme with concern to Growth Progressions in Early Childhood - E. Joseph, J. (Scientific Journal of Medical Science, 2014)
A growing body of evidence suggests that supplementary feeding programs have a positive effect on reducing malnutrition prevalence in developing countries. In India, despite substantial funding of its early childhood development program, which has a large supplementary feeding component, levels of child malnutrition have fallen only slightly. Using propensity score matching to identify impacts in data from the Integrated Child Development Services scheme ICDS collected between 2005 and 2006, this paper finds that India’s ICDS have a significant effect on malnutrition rates. These findings point to the importance of investing in various growth factors and sanitation, and educating the public about hygiene to promote health knowledge and better child outcomes. As importantly, such investments have the potential of making the feeding program more effective.